Small Molecule Inhibitor of Protein Kinase C DeltaI (PKCδI) Decreases Inflammatory Pathways and Gene Expression and Improves Metabolic Function in Diet-Induced Obese Mouse Model - Brenna Osborne; Rekha S. Patel; Meredith Krause-Hauch; Ashley Lui; Gitanjali Vidyarthi; Niketa A. Patel (Biology)
Obesity promotes metabolic diseases such as type 2 diabetes and cardiovascular disease. PKCδI is a serine/threonine kinase which regulates cell growth, differentiation, and survival. Caspase-3 cleavage of PKCδI releases the C-terminal catalytic fragment (PKCδI_C), which promotes inflammation and apoptosis. We previously demonstrated an increase in PKCδI_C in human obese adipose tissue (AT) and adipocytes. Subsequently, we designed a small molecule drug called NP627 and demonstrated that NP627 specifically inhibited the release of PKCδI_C in vitro. Here, we evaluate the in vivo safety and efficacy of NP627 in a diet-induced obese (DIO) mouse model. The results demonstrate that NP627 treatment in DIO mice increased glucose uptake and inhibited the cleavage of PKCδI_C in the AT as well as in the kidney, spleen, and liver. Next, RNAseq analysis was performed on the AT from the NP627-treated DIO mice. The results show increases in ADIPOQ and CIDEC, upregulation of AMPK, PI3K-AKT, and insulin signaling pathways, while inflammatory pathways were decreased post-NP627 administration. Further, levels of lncRNAs associated with metabolic pathways were affected by NP627 treatment. In conclusion, the study demonstrates that NP627, a small-molecule inhibitor of PKCδI activity, is not toxic and that it improves the metabolic function of DIO mice in vivo.